Turnover and heterogeneity in top management networks: A demographic analysis of two Swedish business groups - Sven-Olof Collin; Timurs Umans (International Journal of Business Science & Applied Management (IJBSAM), 2008)
A theory based on the demography of top management teams is used to explain membership turnover in two Swedish business groups, network analysis being used to define group membership. The results suggest these business groups possess a combination of financial and industrial experience as a group resource and the socialising strategy of control as a force counteracting the conflict-producing force of heterogeneity. An organisational demographic perspective focusing on opposing forces of heterogeneity and homogeneity is developed. It is shown that the perspective can be applied both to formal organisations and to informal ones such as networks.
Keywords: 650; top management networks; turnover; heterogeneity; business groups